Islam, Radikalisme dan Deradikalisasi Berbasis Pancasila - Syaiful Arif (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: Religious radicalism (Islam) developed the theological thought to counter-Pancasila and the Republic of Indonesia (NKRI), it can be fought and softened with Pancasila itself. This is due to the fact that the cause of such radicalism is a misunderstanding to the Pancasila and its political system. Pancasila is regarded as a secular political ideology, whereas it actually cared pattern for the relationship between religion and state that upholds the values of divinity on the one side, and the public virtue on the other side. Deradizalisation of religion based on Pancasila can be applied with two strategies. First, proving the existence of religious dimension of Pancasila and Republic of Indonesia to undermine the secular claims from the radical groups. Second, learning the nature of politics which contained in Pancasila. These nature of politics are more in line with the political ideals of Islam, rather than the ideology of Islamism which tends to the violent.Â KEYWORDS:Â Islam, radicalism, deradicalization, Pancasila.